Proteome profiling of home-sampled dried blood spots reveals proteins of SARS-CoV-2 infections - Fredolini, Claudia; Dodig-Crnkovic, Tea; Bendes, Annika; Dahl, Leo; Dale, Matilda; Mattsson, Cecilia; Thomas, Cecilia Engel; Albrecht, Vincent; Torinsson Naluai, Åsa; Gisslen, Magnus; Beck, Olof; Roxhed, Niclas; et al. (Royal Institute of Technology, 2024)
The report contains data on protein levels obtained from dried blood spot (DBS) samples.

The DBS originated from donors who provided self-sampling blood using a sampling kit (Capitainer AB). The studies were conducted in the general population in Stockholm and Gothenburg (Sweden) during the COVID-19 pandemic in the spring of 2020 and 2021:

- Levels of circulating antibodies were determined in the 2021 study by multi-analyte serology using the Luminex platform. Serology data from the 2020 studies have been deposited in a previous submission (https://figshare.scilifelab.se/articles/dataset/Multianalyte_serology_in_home-sampled_blood_enables_an_unbiased_assessment_of_the_immune_response_against_SARS-CoV-2/14555520) . All data sets have been processed and normalized using a linear model described in the publication (https://doi.org/10.1038/s41467-021-23893-4) of the previous submission.
- Levels of circulating proteins were determined by proximity extension assays using three Target96 panels from the Olink platform. The raw NPX data has been processed using AbsPQN, as described in the manuscript related to this submission.
- Other data is provided in the manuscript.
Access to this individual-level human data can be granted for non-commercial validation purposes and upon reasonable request to the provided contact. A reasonable request should contain the following:

- Name of PI and host organization
- Contact details
- The scientific purpose of the data access request
- Commitment to inform when the data has been used in a publication
- Commitment not to host or share the data outside the requesting organization
- Statement of non-commercial use of data
Keywords: Medical biochemistry - proteins and peptides (incl. medical proteomics); Humoural immunology and immunochemistry; Infectious diseases; Medical and Health Sciences; Medicin och hälsovetenskap; Infectious Medicine; Infektionsmedicin; Immunology; Immunologi; Medical Biotechnology (Focus on Cell Biology, (incl. Stem Cell Biology), Molecular Biology, Microbiology, Biochemistry or Biopharmacy); Medicinsk bioteknologi (inriktn. mot cellbiologi (inkl. stamcellsbiologi), molekylärbiologi, mikrobiologi, biokemi eller biofarmaci)